Cooling of a rectangular microchannel heat sink with ammonia gas - Adham, Ahmed Mohammed (American Institute of Physics, 2012)

(untitled)
The increased global demands for the minimization of integrated circuits used in electronic devices have led manufacturing companies to direct their resources towards research in that area. The minimization processes provided very powerful electronic chips but with a very large amount of heat generation. One of the methods applied to remove the heat produced is to use a microchannel heat sink. Past optimization attempts have looked at the microchannel geometry, material, and coolant types using various models to represent the heat sink. This paper reports the analytical study on the optimization of the thermal resistance and pressure drop of a rectangular microchannel heat sink using a new coolant, ammonia gas. The effect of different channel aspect ratio was investigated. Significant reduction in thermal resistance was obtained with 0.218 K/W for ammonia gas compared to that of 0.266 k/W for air under the same operating conditions. The total pressure drop achieved was 5.36 mbar and 9.52 mbar for ammonia and air respectively. The results indicate promising potential for ammonia gas as a coolant for rectangular microchannel heat sink.